Assessment of Acupuncture and Moxibustion Medicine Clinical Practice Using the Objective Structured Clinical Examination - Eunbyul Cho; Ju-Hyun Lee; O Sang Kwon; Jiseong Hong; Nam Geun Cho (MEDrang Inc., 2021)
Background The objective structured clinical examination (OSCE) is a widely used method to assess the clinical performance of students in clinical practice. Although OSCE has been used for undergraduate students of Korean medicine, this has not been widely reported. Methods In 2020, the practical course for acupuncture and moxibustion medicine (acupuncture, electroacupuncture, pharmacopuncture, auricular acupuncture, and burning acupuncture) was taught using flipped learning, according to clinical practice guidelines, and assessed by the OSCE. The appropriateness of this model of education and its evaluation using OSCE were evaluated using a 5-point Likert scale, and the results were analyzed. Results Of the respondents, 67% reported that the OSCE accurately reflected their competency, and 82% reported that online video lectures helped them to improve their clinical skills. The average adequacy score of the model was > 3.7/5, and the average adequacy score of the checklist used in the OSCE was > 4.1/5 for all 5 clinical application skills. The difference in the mean self-efficacy score between students who had taken the OSCE and those students who had not taken the OSCE, was highest in the burning acupuncture group (0.923). Conclusion This study showed that students' satisfaction with the OSCE was high and flipped learning was an effective education model. In the future, models representing the human body or simulated patients should be used to evaluate students' skills and attitude.